2007
DOI: 10.1152/japplphysiol.00486.2007
|View full text |Cite
|
Sign up to set email alerts
|

Brain stem NO modulates ventilatory acclimatization to hypoxia in mice

Abstract: The objective of our study was to assess the role of neuronal nitric oxide synthase (nNOS) in the ventilatory acclimatization to hypoxia. We measured the ventilation in acclimatized Bl6/CBA mice breathing 21% and 8% oxygen, used a nNOS inhibitor, and assessed the expression of N-methyl-d-aspartate (NMDA) glutamate receptor and nNOS (mRNA and protein). Two groups of Bl6/CBA mice (n = 60) were exposed during 2 wk either to hypoxia [barometric pressure (PB) = 420 mmHg] or normoxia (PB = 760 mmHg). At the end of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…These data indicated a role for adiponectin in upregulating NOS in non-parenchymal cells. Since NO metabolism is rapid (t 1/2 =4 s) in vivo and the final products are nitrite (NO 2− ) and nitrate (NO 3− ), the best index of total NO production is the sum of both NO 2− and NO 3− [24]. Thus, we quantified total NO 2− and NO 3− using a fluorometric assay.…”
Section: Resultsmentioning
confidence: 99%
“…These data indicated a role for adiponectin in upregulating NOS in non-parenchymal cells. Since NO metabolism is rapid (t 1/2 =4 s) in vivo and the final products are nitrite (NO 2− ) and nitrate (NO 3− ), the best index of total NO production is the sum of both NO 2− and NO 3− [24]. Thus, we quantified total NO 2− and NO 3− using a fluorometric assay.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, NTS-specific NOS antagonism blunts the potassium cyanide-mediated increase in breathing at 5 and 10 min but not 30 min after treatment (134), and prevents the acute HVR after 1 minute (287). Conversely, others have reported that systemic or NTS-specific nNOS inhibition does not block STP in conscious mice (83), or rats (301). However, since this pathway is a common form of short-term synaptic plasticity that is conserved at glutamatergic synapses throughout the CNS, it is likely that enhanced synaptic sensitivity due to the activation of this pathway occurs not only at the synapse between the carotid body and the NTS, but also at the synapses between NTS secondary neurons and other respiratory centers in the CNS.…”
Section: Physiological and Molecular Responses To Brief Hypoxic Exposmentioning
confidence: 94%
“…Indeed, in other areas of the CNS, it has been demonstrated that with prolonged activation of the canonical glutamate/NO LTP pathway, the expression of involved proteins, such as NMDARs and nNOSs increase to further enhance the sensitivity of the system (10). Similarly, in mice and rats exposed to chronic hypoxia, the expression of phosphorylated AMPAR and NMDAR subunits and also nNOS increase in the NTS (83, 299, 301, 335, 434). Overall though, while there is clear evidence that glutamatergic neurotransmission is central to the CNS component of VAH, the role of NO and nNOS in mediating this effect remains controversial, and results to date point at potential species differences.…”
Section: Physiological and Molecular Responses To Prolonged Hypoxic Ementioning
confidence: 97%
See 1 more Smart Citation
“…Selective inhibition nNOS in the brainstem has no effect on ventilation or the HVR in control mice but it decreases ventilation in chronically hypoxic mice (Hasnaoui-Saadani et al, 2007). Hence, effects of HIF-1α on NO appear to enhance O 2 delivery from effects on ventilation in chronic hypoxia, as well as from the effects of NO-induced vasodilation on vascular O 2 delivery.…”
Section: Potential Mechanisms For Plasticity Induced By Hif-1αmentioning
confidence: 99%